Construction and Practical Paths of the Multi-Dimensional Linkage Ideological and Political Class Model - Wang, Hongwei; Ren, Jinfeng; Feng, Zhanji (Journal of Research in Vocational Education, 2025)
This paper aims to address the practical issue of how to effectively integrate “forging a strong sense of community for the Chinese nation” into the fundamental task of “fostering virtue through education” in higher education institutions. In response to systemic dilemmas such as theoretical disconnection, fragmented practice, and lack of evaluation mechanisms in current integration practices, this study comprehensively adopts literature review, empirical investigation, and action research methods to construct a multi-disciplinary theoretical framework, design a three-level evaluation index system covering “cognition-emotion-behavior”, and propose a practical model of “multi-dimensional linkage ideological and political class”. The core of this model lies in achieving “three collaborative linkages”: the joint efforts of ideological and political courses and curriculum-based ideological and political education; the synergistic efficiency of the first class and the second class to deepen cognitive and emotional identification; and the two-way extension of the university’s small class and society’s big class, constructing a practical system integrating online and offline, research, publicity and assistance.